International trade and business cycle synchronization in Poland, the European Union and the Euro Zone - Piotr Misztal (Contemporary Economics, 2013)
The analysis of business cycle synchronization levels has become a key point in the discussion of the processes of international economic integration. Economists show a particular interest in analyzing the frequency of processes of business cycle convergence and divergence (decoupling) in the European Union, especially in the Euro Zone. One of the factors determining business cycle convergence in economies is the intensity and structure of international trade. The aim of this paper is to analyze the influence exerted by international trade over the synchronization of business cycles in Poland, the European Union and the Euro Zone from 1995 to 2011. The analytical methods employed here encompass a review of the literature on macroeconomics and international finance, as well as econometric models (such as the Vector Autoregression Model). The results of empirical research indicate that an increase in trade turnover does not necessarily lead to greater business cycle synchronization in the economies under analysis. In fact, the impact of an increase in countries' turnover on the synchronization of their business cycles depends predominantly on the structure of trade turnover and not solely on the intensity of trade.
Keywords: E32; F14; F15; 330; business cycle; international trade; economic integration